Application of iron-doped barium titanate nanoparticles in piezoelectric catalytic nitrogen reduction
By using iron-doped barium titanate nanoparticles for piezoelectric catalysis under ultrasonic vibration, the problems of high temperature, high pressure and low efficiency in the existing nitrogen conversion process are solved, and the efficient nitrogen reduction and conversion effect is achieved.
Patent Information
- Application Number
- CN202411539217.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-29
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Existing ammonia production processes such as the Haber-Bosch process operate under high temperature and high pressure, with large energy consumption and environmental pollution, and lack of reaction sites in the nitrogen conversion reaction and low charge carrier utilization, making it difficult to effectively catalyze nitrogen reduction.
Iron-doped barium titanate nanoparticles are used as catalysts to perform piezoelectric catalytic nitrogen reduction under ultrasonic vibration to achieve the production of ammonium roots.
The nitrogen-fixing efficiency of iron-doped barium titanate nanoparticles in piezoelectric catalytic nitrogen reduction reached 66.72 μmol·g-1·h-1, which is much higher than the nitrogen-fixing ability of existing piezoelectric materials, and the catalytic performance is stable.
Smart Images

Figure CN119565614A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic nanomaterials and piezoelectric catalysis, and in particular to a preparation method of iron-doped barium titanate nanoparticles and application thereof in piezoelectric catalytic nitrogen reduction. Background Art
[0002] Nitrogen is the most abundant element in the Earth's atmosphere and a key element for organisms to sustain life. Converting nitrogen into value-added products is of great significance for improving life and sustainable development. Today, most ammonia is produced by the Haber-Bosch process, which has become one of the basic pillars of today's chemical industry. In order to break the stable N≡N bond, the Haber-Bosch process usually operates at high temperature and pressure, and requires ultra-pure H2 as a raw material. However, most of the hydrogen sold on the market is produced by natural gas reforming, and only about 1% comes from hydrocatalysis. Natural gas reforming uses fossil fuels, consumes a lot of energy, and emits greenhouse gases. Therefore, it is of great significance to develop an alternative method for ammonia production to replace the dangerous, energy-intensive and unsustainable Haber-Bosch process.
[0003] Currently, many studies focus on the direct conversion of ammonia from nitrogen and water under ambient conditions using light or electricity. The main challenge of these direct conversions is the high energy barrier required for nitrogen activation: the cleavage of the first bond in the nitrogen molecule requires a reduction potential of -4.16 V (compared to NHE). Currently, the research on piezoelectric-driven nitrogen fixation is in its infancy, and the main challenge of most piezoelectric materials is their lack of reactive sites for nitrogen conversion and the low utilization of piezoelectrically generated charge carriers. Therefore, it is crucial to design materials with excellent piezoelectric properties and excellent catalytic activity to fix nitrogen. Summary of the invention
[0004] The purpose of the present invention is to provide an inorganic nanomaterial of iron-doped barium titanate nanoparticles and a preparation method thereof, which can realize piezoelectric catalytic reduction of nitrogen into ammonium radicals under the action of ultrasonic vibration. Experiments have shown that the nitrogen fixation and ammonia conversion efficiency of barium titanate (Fe-BTO-3) with a 3% iron doping ratio reaches 66.72 μmol·g -1 ·h -1 (830 μmol·L -1 ·g -1 ·h -1 ), which is much higher than the nitrogen fixation ability of the currently reported piezoelectric material ZnO.
[0005] To achieve the above object, the specific technical solution of the present invention is as follows: Application of iron-doped barium titanate nanoparticles in catalytic nitrogen reduction.
[0006] Application of iron-doped barium titanate nanoparticles in piezoelectric catalytic nitrogen reduction.
[0007] Application of iron-doped barium titanate nanoparticles in catalytic reduction of nitrogen to ammonium or ammonia.
[0008] Preferably, the above application is carried out under light-proof conditions; the temperature of the above application is room temperature, such as 0 to 50°C, preferably 10 to 40°C, and further preferably 15 to 30°C.
[0009] Preferably, in the iron-doped barium titanate nanoparticles, the molar fraction of iron ions relative to titanium ions is 1% to 5%, and preferably, the molar fraction of iron ions relative to titanium ions is 2% to 4%.
[0010] The invention discloses a method for preparing the above-mentioned iron-doped barium titanate nanoparticles, comprising the following steps: reacting an iron source, a titanium source and a barium source in a solution to obtain the iron-doped barium titanate nanoparticles; specifically, placing the iron source in a precursor solution containing a titanium source and a barium source, centrifuging and washing after the reaction, and drying to obtain the iron-doped barium titanate nanoparticles.
[0011] Preferably, in the precursor solution containing a titanium source and a barium source, the molar ratio of titanium to barium is 1:0.5 to 1.5, preferably 1:0.8 to 1.4.
[0012] Preferably, the reaction temperature is 120-160° C. and the reaction time is 6-24 hours.
[0013] The invention discloses a method for catalyzing nitrogen reduction, which comprises the following steps: using the iron-doped barium titanate nanoparticles to catalyze nitrogen reduction.
[0014] The invention discloses a method for catalyzing nitrogen reduction to produce ammonia or ammonium radicals, comprising the following steps: using the iron-doped barium titanate nanoparticles to catalyze nitrogen reduction to produce ammonia or ammonium radicals.
[0015] In the present invention, the catalytic nitrogen reduction is piezoelectric catalytic nitrogen reduction, which does not require light irradiation; specifically, a solution containing iron-doped barium titanate nanoparticles and nitrogen is ultrasonically treated, and piezoelectric catalytic nitrogen reduction is performed to achieve the generation of ammonium radicals.
[0016] Advantages of the present invention: The invention discloses the preparation of iron-doped barium titanate nanoparticles and the application of the iron-doped barium titanate nanoparticles in piezoelectric catalysis of nitrogen reduction to ammonia. The iron-doped barium titanate nanoparticles have the advantages of stable and excellent catalytic performance and simple method when piezoelectric catalysis of nitrogen reduction to ammonia; and the iron-doped barium titanate nanoparticles have enhanced piezoelectric response when piezoelectric catalysis of nitrogen reduction to ammonia.
[0017] The present invention discloses for the first time a method for applying iron-doped barium titanate nanoparticles to piezoelectric nitrogen fixation, which effectively enhances the adsorption of nitrogen and, combined with excellent piezoelectric properties, enables the material to have good nitrogen fixation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a transmission electron microscopy image of Fe-BTO-3 nanoparticles.
[0019] Figure 2 This is a diagram showing the effect of piezoelectric catalytic nitrogen reduction of barium titanate nanoparticles and Fe-BTO-x.
[0020] Figure 3 This is the relationship curve between Fe-BTO-3 piezoelectric catalytic nitrogen reduction and time.
[0021] Figure 4 These are the X-ray diffraction patterns and transmission electron microscopy images of the Fe-BTO-3 piezoelectric catalytic nitrogen reduction experiment after 5 cycles. DETAILED DESCRIPTION
[0022] The present invention discloses an application of iron-doped barium titanate nanoparticles in piezoelectric catalytic nitrogen reduction to ammonia. Pure barium titanate nanoparticles and iron-doped barium titanate nanoparticles (Fe-BTO) are obtained by a simple solvothermal method, and piezoelectric catalytic nitrogen reduction to ammonium ions or ammonia is achieved under ultrasonic vibration.
[0023] The present invention obtains pure barium titanate nanoparticles (BTO) and barium titanate nanoparticles with different iron doping amounts (Fe-BTO-x, x=1-5, preferably 1, 3, 5) by a simple solvent thermal method.
[0024] The invention discloses a method for reducing ammonia with iron-doped barium titanate nanoparticles under piezoelectric catalysis of nitrogen, comprising the following steps: during nitrogen reduction, the iron-doped barium titanate nanoparticles are placed in deionized water and nitrogen is introduced, followed by ultrasonic treatment, and the generation of ammonium radicals is detected by Nessler reagent colorimetric method.
[0025] The preparation method of the iron-doped barium titanate nanoparticles of the present invention comprises the following steps: placing an iron source in a precursor solution containing a titanium source and a barium source, centrifuging and washing after reaction, and drying to obtain the iron-doped barium titanate nanoparticles.
[0026] In the present invention, tetrabutyl titanate (C 16 H 36 O4Ti) as a titanium source, and barium nitrate (Ba(NO3)2) as a barium source, which are dissolved in n-butanol and deionized water, respectively, to obtain a precursor solution containing a titanium source and a barium source; C 16 H 36 The molar ratio of O4Ti to Ba(NO3)2 is 1:0.8, 1:1, 1:1.2 and 1:1.4. Preferably, C 16 H 36The molar ratio of O4Ti to Ba(NO3)2 is 1:1; the solvent thermal reaction is carried out in a reactor at 120-160°C for 6-24 hours, and the preferred condition is 135°C for 18 hours.
[0027] In the present invention, on the basis of the preparation method of barium titanate nanoparticles, an iron source is added as a dopant, and barium titanate nanoparticles (Fe-BTO-x) with different iron doping amounts are prepared by controlling the amount of iron element. Specifically, nonahydrated iron nitrate (Fe(NO3)3·9H2O) is selected as the iron source, and the molar fraction of iron ions relative to titanium ions is 1%, 3% and 5%. Preferably, the molar fraction of iron ions is 3%.
[0028] As an example, the present invention adds the above-mentioned pure BTO and Fe-BTO (50 mg each) into 100 mL of deionized water, and introduces nitrogen after vacuuming. The flow rate of nitrogen is 20, 30 and 40 mL / min, and the preferred condition is 30 mL / min. The purpose of reducing nitrogen to ammonium ions is achieved under ultrasonic vibration.
[0029] The following experiments illustrate the technical progress of the present invention. The raw materials involved are conventional products in the field, and the specific preparation operations and performance tests are all conventional techniques.
[0030] Example 1 Preparation of pure barium titanate nanoparticles, the specific steps are as follows: (1) Weigh 522.7 mg of barium nitrate and dissolve it in 10 mL of deionized water. Disperse by ultrasonication. (2) Weigh 1 g of NaOH and add it to 10 mL of deionized water; (3) Take 0.68 mL of tetrabutyl titanate solution and drop it into 10 mL of n-butanol solution, and stir to mix; (4) Add 5 mL of oleic acid to 10 mL of n-butanol; The above four solutions were mixed in sequence to obtain a white milky solution, which was moved to a 100 mL high-pressure reactor after stirring and reacted at 135°C for 18 hours. After the reaction, the product was washed six times with ethanol: water = 1:1 solution, washed once with 5% acetic acid in the middle, and finally dried at 60°C for 12 h to obtain pure barium titanate nanoparticles.
[0031] Example 2 Preparation of Fe-BTO-3 nanoparticles, the specific steps are as follows: (1) Weigh 522.7 mg of barium nitrate and 24.24 mg of ferric nitrate nonahydrate and dissolve them in 10 mL of deionized water. Disperse by ultrasonication. (2) Weigh 1 g of NaOH and add it to 10 mL of deionized water; (3) Take 0.66 mL of tetrabutyl titanate solution and drop it into 10 mL of n-butanol solution, and stir to mix; (4) Add 5 mL of oleic acid to 10 mL of n-butanol; The above four solutions were mixed in sequence to obtain a white milky solution, which was moved to a 100 mL high-pressure reactor after stirring and reacted at 135°C for 18 hours. After the reaction, the product was washed six times with ethanol: water = 1:1 solution, washed once with 5% acetic acid in the middle, and finally dried at 60°C for 12 h to obtain Fe-BTO-3 nanoparticles with a molar fraction of iron ions of 3%.
[0032] Attached Figure 1 This is a transmission electron microscope image of the above-mentioned Fe-BTO-3 nanoparticles. From the image, it can be seen that the particle size of the Fe-BTO-3 nanoparticles is about 10 nm.
[0033] Example 3 Preparation of Fe-BTO-1 nanoparticles, the specific steps are as follows: (1) Weigh 522.7 mg of barium nitrate and 8.08 mg of ferric nitrate nonahydrate and dissolve them in 10 mL of deionized water. Disperse by ultrasonication. (2) Weigh 1 g of NaOH and add it to 10 mL of deionized water; (3) Take 0.673 mL of tetrabutyl titanate solution and drop it into 10 mL of n-butanol solution, and stir to mix; (4) Add 5 mL of oleic acid to 10 mL of n-butanol; The above four solutions were mixed in sequence to obtain a white milky solution, which was moved to a 100 mL high-pressure reactor after stirring and reacted at 135°C for 18 hours. After the reaction, the product was washed six times with ethanol: water = 1:1 solution, washed once with 5% acetic acid in the middle, and finally dried at 60°C for 12 h to obtain Fe-BTO-1 nanoparticles.
[0034] Example 4 Preparation of Fe-BTO-5 nanoparticles, the specific steps are as follows: (1) Weigh 522.7 mg of barium nitrate and 40.40 mg of ferric nitrate nonahydrate and dissolve them in 10 mL of deionized water. Disperse by ultrasonication. (2) Weigh 1 g of NaOH and add it to 10 mL of deionized water; (3) Take 0.646 mL of tetrabutyl titanate solution and drop it into 10 mL of n-butanol solution, and stir to mix; (4) Add 5 mL of oleic acid to 10 mL of n-butanol; The above four solutions were mixed in sequence to obtain a white milky solution, which was moved to a 100 mL high-pressure reactor after stirring and reacted at 135°C for 18 hours. After the reaction, the product was washed six times with ethanol: water = 1:1 solution, washed once with 5% acetic acid in the middle, and finally dried at 60°C for 12 h to obtain Fe-BTO-5 nanoparticles.
[0035] Example 5 Experiment on piezoelectric catalytic nitrogen reduction using different catalysts 50 mg of the catalyst was dispersed in 100 ml of deionized water in a glass reactor, and the reactor was fixed in an ultrasonic cleaner (45 kHz, power: 300 W). After evacuation, the solution was bubbled with pure N2 for 0.5 h in the dark, and then ultrasonic vibration was started at a fixed temperature (20 °C). 5 ml of the suspension was taken every 1 h, and the ammonia concentration was checked by Nessler reagent colorimetric method.
[0036] The catalysts are pure barium titanate, Fe-BTO-1, Fe-BTO-3 and Fe-BTO-5, and their nitrogen reduction effects are shown in the figure below. Figure 2 As shown; Figure 3 The relationship between Fe-BTO-3 piezoelectric catalytic nitrogen reduction and time. The nitrogen fixation to ammonia conversion efficiency of 3% iron-doped barium titanate (Fe-BTO-3) reached 66.72 μmol·g -1 ·h -1 (equivalent to 830 μmol·L -1 ·g -1 ·h -1 ), which is 7.5 times that of pure BTO, and its performance is much higher than the nitrogen fixation capacity of the currently reported piezoelectric material ZnO (3.60 μmol·g -1 ·h -1 ).
[0037] Example 6 Fe-BTO-3 structural stability test The material recovered after 4 h of ultrasound in Example 6 was washed with deionized water and 95% ethanol in turn, dried in a vacuum oven, and then redispersed in 100 ml of deionized water in a glass reactor. The reactor was fixed in an ultrasonic cleaner (45 kHz, power: 300 W). After evacuation, the solution was bubbled with pure N2 in the dark for 0.5 h, and then ultrasound was started at a fixed temperature (20°C). 5 ml of the suspension was taken every 1 h, and the ammonia concentration was checked by Nessler reagent colorimetry. The above steps were repeated 5 times to separate the material, and the morphology of the sample was characterized by transmission electron microscopy, and the structure of the material was characterized by X-ray diffraction (XRD) spectrum. As shown in the attached figure Figure 4As shown in the figure, the material morphology still maintains a nanoparticle structure of about 10 nm, and the XRD peak does not change. Therefore, the catalyst can be reused and has good structural stability.
[0038] The present invention discloses for the first time a method for preparing inorganic perovskite nanomaterials that uses mechanical energy vibration to reduce nitrogen without illumination. Experiments have shown that the nitrogen fixation to ammonia conversion efficiency of 3% iron-doped barium titanate (Fe-BTO-3) reaches 66.72 μmol·g -1 ·h -1 (830 μmol·L -1 ·g -1 ·h -1 ), which is much higher than the nitrogen fixation capacity of piezoelectric materials reported so far.
Claims
1. Application of iron-doped barium titanate nanoparticles in catalytic nitrogen reduction.
2. Application of iron-doped barium titanate nanoparticles in piezoelectric catalytic nitrogen reduction.
3. Application of iron-doped barium titanate nanoparticles in catalytic reduction of nitrogen to ammonia or ammonium ions.
4. The use according to claim 1, 2 or 3, characterized in that: In the iron-doped barium titanate nanoparticles, the molar fraction of iron ions relative to titanium ions is 1% to 5%.
5. The use according to claim 1, 2 or 3, characterized in that: The method for preparing the iron-doped barium titanate nanoparticles comprises the following steps: reacting an iron source, a titanium source and a barium source in a solution to obtain the iron-doped barium titanate nanoparticles.
6. The use according to claim 5, characterized in that: In the precursor solution containing a titanium source and a barium source, the molar ratio of titanium to barium is 1:0.5-1.
5.
7. The use according to claim 5, characterized in that: The reaction temperature is 120-160°C and the reaction time is 6-24 hours.
8. A method for catalytic nitrogen reduction, comprising the following steps: catalyzing nitrogen reduction with the iron-doped barium titanate nanoparticles according to claim 1.
9. A method for catalyzing the reduction of nitrogen to produce ammonia or ammonium radicals, comprising the following steps: using the iron-doped barium titanate nanoparticles as claimed in claim 1 to catalyze the reduction of nitrogen to produce ammonia or ammonium radicals.
10. The method according to claim 8 or 9, characterized in that: The catalytic nitrogen reduction is piezoelectric catalytic nitrogen reduction.
Citation Information
Patent Citations
Piezoelectric element, multilayered piezoelectric element, liquid discharge head, liquid discharge apparatus, ultrasonic motor, optical apparatus, and electronic apparatus
CN107651956A
Preparation method of black-oxide barium titanate material
CN110065966A
Barium titanate-based leadless piezoelectric ceramic and preparation method thereof
CN116477938A
Application of metal sulfide piezoelectric material in piezoelectric catalytic reduction of CO2
CN116791112A
Ultrafine metal oxide production
WO2005097705A1